Prospects for alternative energy development in the U.S. West : tilting at windmills? - Pierce, John C.; Steel, Brent (Springer, 2017)
This book poses the question of whether identifiable individual-level attributes (e.g., values, interests, knowledge, demographic characteristics) lead to support for or opposition to the development and implementation of alternative energy technologies. In recent years, attempts to site alternative energy technologies (e.g., wind, solar, wave) have been met by intense opposition from a variety of sources, including many environmentalists from whom one might expect support for non-carbon based renewable energy initiatives. This volume argues that there are indeed such discernible attributes, and moreover that the identification and exploration are important for the development of support strategies for the well-informed and achievable siting of such technologies.
Keywords: Renewable energy sources -- West (U.S.); West United States.; elektronické knihy; electronic books